Prototype of Automatic Control System for Water Temperature and Acidity in Ornamental Fish Aquarium Based on Internet of Things (IOT) - Hermansyah, Adi; Septian, Tri Wanda; P, Aditya Putra Perdana; Faris, Mgs Muhammad (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2023)
The Internet of Things (IoT) has brought changes to modern life, such as automatic traffic lights, smart homes, optimizing energy utilization, and monitoring water conditions in ornamental fish. It is necessary to design an integrated system that can monitor and maintain stable water conditions and is suitable for ornamental fishing. This paper describes the design of an automatic control system tool for regulating water temperature and acidity in an IoT-based fish aquarium. The design of the tool consists of a NodeMCU ESP 8266 as the microcontroller, connected to DS18B20 to measure water temperature, and PH-4502C to measure acidity. The application of the control system in the aquarium works well, with an average temperature of 28.99 centigrade and a pH of 5.44.